STRATIGRAPHIC VARIATION OF COMPLEX IMPURITIES IN PLATFORM LIMESTONES AND POSSIBLE SIGNIFICANCE OF ATMOSPHERIC DUST: A STUDY WITH EMPHASIS ON GAMMA-RAY SPECTROMETRY AND MAGNETIC SUSCEPTIBILITY OUTCROP LOGGING (EIFELIAN-FRASNIAN, MORAVIA, CZECH REPUBLIC) - Hladil J.; Gersl M.; Strnad L.; Frana J.; Langrova A.; Spisiak J. (My University, 2006)
Mineral dust and other constituents of Devonian atmospheric aerosols together with certain amounts of aquatic suspensions of riverine detrital origin, colloidal particle dispersions and seawater solutes were embedded in ~95–98% (or purer) limestones on a consistently subsiding isolated carbonate platform where they formed very complex impurity systems. Very low Th/U values, relative abundance of Fe but a slight excess of K typically characterize these ultrafine impurities which are mineralogically dominated by smectite–illite and mica (sericite) together with goethite. In vertical section, these impurities are arranged like incremental series of light and dense bands. The combined method of natural gamma-ray spectrometric and magnetic susceptibility measurements (GRS–MS) together with background of major and trace element analyses provided first systematic insights into fine-scale variability of these impurities in a pile of pure carbonate platform beds, mostly in inner platform Amphipora limestone facies. These carbonates were deposited close to sea level but far from river mouths, and they represented a certain sort of a relatively “independent” medium that was primarily sensitive to climatically (and by rare events) controlled input of atmospheric dust. A remarkable similarity of MS stratigraphic patterns that reflect the quantity and quality of embedded impurities in very distant and paleogeographically separated Devonian basins might be seen as supporting this viewpoint. A long composite stratigraphic section of the Moravian Karst ranges from mid-Eifelian to end-Frasnian levels and yields a number of time characterizing GRS–MS variations that can potentially serve as templates for high-resolution stratigraphic correlations over long distances.
Keywords: COMPLEX IMPURITIES; PLATFORM LIMESTONES; GAMMA-RAY SPECTROMETRY; MAGNETIC SUSCEPTIBILITY; DEVONIAN; Paleozoic::Devonian; Палеозой::Девонская